The Role of the Pati Regency Youth, Sports, and Tourism Office in Empowering Bakaran Wetan Tourism Village to Increase Local Own-Source Revenue under Pati Regent Regulation Number 28 of 2022 on Tourism Village Empowerment - Ipang Danareo; Ikomatussuniah Ikomatussuniah; Ahmad Rayhan (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Tourism village empowerment has become a strategic regional policy for increasing Local Own-Source Revenue (LOR) through the utilization of local cultural assets. Bakaran Wetan Tourism Village in Pati Regency is developed under Pati Regent Regulation Number 28 of 2022, yet its implementation remains constrained by limited funding, weak institutional coordination, declining tourist interest, and the tourism sector's modest contribution to regional revenue. This study analyzes the implementation, constraints, and optimization strategies of the Pati Regency Youth, Sports, and Tourism Office (DINPORAPAR) in empowering Bakaran Wetan Tourism Village. An empirical juridical approach with qualitative methods was employed using semi-structured interviews with government officials, Batik Bakaran artisans, local residents, and tourists, supported by legal and documentary analysis. The findings show that DINPORAPAR has implemented tourism village assessment, institutional guidance, tourism promotion, batik training, and community-based cultural development as unilateral governmental legal actions. Policy implementation remains constrained by weak inter-agency coordination and limited tourism funding. Batik training and digital marketing effectively strengthen community capacity while preserving cultural authenticity, whereas batik printing assistance is less effective because it overlooks the traditional identity of hand-drawn Batik Bakaran.